Determinação de fumonisina B1 por CLAE: estudo da estabilidade do derivado fumonisina B1-orto-ftaldialdeído - Petrarca, Mateus Henrique [UNESP]; Rossi, Elizeu Antonio [UNESP]; Sylos, Celia Maria de [UNESP] (My University, 2012)
The present study aimed at evaluating the stability of fumonisin B1 -ortho-phthaldialdehyde derivative under different conditions of pH, time and temperature, during the derivatization reaction and chromatographic analysis. In the derivatization, the maximum fluorescence emitted by the derivative product was obtained employing a 0.1 M sodium tetraborate solution at pH 9.0, and this did not differ significantly from those emitted at pH 8.0, 8.5, 9.5 and 10.0. Within 2 minutes of reaction, the maximum fluorescence was observed and no significant difference was found when compared with those emitted at 4, 6 and 8 minutes of reaction. The 0.5 unit variation in the pH of 0.1 M sodium phosphate buffer solution, which was used as mobile phase, caused a significant effect on the chromatographic separation and on the fumonisin B1 -ortho-phthaldialdehyde derivative detection. The highest fluorescence intensities were found at pH from 3.3 to 3.8. Reduction in the fluorescence intensity was causes by increasing the chromatographic column temperature. The fumonisin B1 -ortho-phthaldialdehyde derivative remained stable from 20 ºC to 27 ºC. At 30 °C, it was found a significant reduction in 26.5% in the fluorescence intensity emitted by the derivative product.

Este estudo avaliou a estabilidade do derivado fumonisina B1 -orto-ftaldialdeído sob diferentes condições de pH, tempo e temperatura, durante a reação de derivatização e as análises cromatográficas. Na derivatização, a máxima fluorescência emitida pelo derivado foi obtida empregando-se a solução de tetraborato de sódio 0,1 M em pH 9,0, e esta não diferiu significativamente das emitidas em pH 8,0, 8,5, 9,5 e 10,0. Em 2 minutos de reação, obteve-se a máxima fluorescência, e esta não diferiu significativamente das emitidas em 4, 6 e 8 minutos de reação. A variação de 0,5 unidade no pH da solução tampão fosfato de sódio 0,1 M, empregada como fase móvel, influenciou significativamente na separação cromatográfica e na detecção do derivado fumonisina B1 -orto-ftaldialdeído; em pH entre 3,3 e 3,8, obtiveram-se as maiores intensidades de fluorescência. O aumento na temperatura da coluna cromatográfica resultou na redução de intensidade da fluorescência. O derivado fumonisina B1 -orto-ftaldialdeído manteve-se estável entre 20 e 27 °C. A 30 °C, houve redução significativa em 26,5% na intensidade da fluorescência emitida pelo derivado.
Determination of fumonisin B1 by HPLC: stability study of the fumonisin B1-ortho-phthaldialdehyde derivative
Keywords: Fumonisin B1; Ortho-phthaldialdehyde; Stability; HPLC; Precolumn derivatization; Fumonisina B1; Orto-ftaldialdeído; Estabilidade; CLAE; Derivatização pré-coluna